Growing Up Online Through Divorce: Child Influencers and Family Change in Indonesia - Ariane Utomo (Social Media + Society, 2025)
Drawing upon divorce cases of Indonesian celebrities with children, I explore the growing online visibility of childhood during and after parental separation. Using a socio-demographic perspective, I examine how rising divorce rates in Indonesia intersect with the increasing portrayals of diverse family structures on social media like Instagram. On one hand, the online visibility of child influencers from divorced celebrity families challenges hegemonic portrayals of the ideal nuclear family, once propagated by the New Order government before its fall in 1998. By amplifying fragments of complex household structures, these child influencers, along with those who have since grown up, have the potential to shape public attitudes and foster greater acceptance of family diversity. On the other hand, it remains uncertain whether this online visibility reduces or inadvertently reinforces the stigma surrounding divorce and growing up through divorce.